Search for New Phenomena in Dijet Angular Distributions in Proton-Proton Collisions at sqrt[s]=8 TeV Measured with the ATLAS Detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (Physical review letters, 2015)
A search for new phenomena in LHC proton-proton collisions at a center-of-mass energy of sqrt[s]=8 TeV was performed with the ATLAS detector using an integrated luminosity of 17.3 fb^{-1}. The angular distributions are studied in events with at least two jets; the highest dijet mass observed is 5.5 TeV. All angular distributions are consistent with the predictions of the standard model. In a benchmark model of quark contact interactions, a compositeness scale below 8.1 TeV in a destructive interference scenario and 12.0 TeV in a constructive interference scenario is excluded at 95% C.L.; median expected limits are 8.9 TeV for the destructive interference scenario and 14.1 TeV for the constructive interference scenario.